General public views, attitudes, and experiences toward drug safety in Dubai, United Arab Emirates: a qualitative approach - Alkhalidi, Doaa; Jamshed, Shazia Qasim; Mohamed Elkalmi, Ramadan; Baig, Mirza Rafi; Aslam, Adeel; Hassali, Mohamed Azmi (MDPI, 2019)
Ensuring drug safety among the patients is the main domain of pharmacovigilance activities worldwide. A pharmacovigilance system was established in the United Arab Emirates (UAE) in 2008. Research evidence reflects that the current system is lacking in active participation from patients, and also, the inadequate role of healthcare professionals is anticipated. In this context, it is pertinent to know the general public’s understandings and their patterns of safe use of medication, which are unexplored areas in Dubai, UAE. The current study aimed to explore the public views, attitudes, and experiences toward medication safety, and to explore key factors enhancing the safe use of medications among the public in Dubai. This study adopted a qualitative approach and face-to-face, 14 in-depth interviews with public individuals, selected purposively using the snowball sampling technique. The interviews were conducted in different places in Dubai recorded and transcribed verbatim and thematically analyzed for data analysis. Reporting of adverse drug reaction was not well-known among all the participants. Public views towards safe use of medicines were limited to the side effects of the consumed medicines only, and to a lesser extent to the inappropriate indication and dosage. Most of the participants mentioned that gaining knowledge about the side effects of the prescribed drug was the main reason for reading the patient information leaflet. Quite a few participants have experienced side effects while consuming their medicines and they were unsure of how to deal with the situation. The current research also reflected the lack of proper communication between pharmacists and physicians in managing drug safety issues. Conclusively, the current research revealed gaps in public views regarding medication’s safety, which consequently may impact their attitudes during the course of medication use. Efforts need to be strengthened to enhance positive views and attitudes of the public towards medication safety and ADR reporting in the UAE.